Determination of Dehydration Pattern and Sensory Properties variation of Blanched and Un-blanched, Cut and Whole Moringa olifera Leaves - Rathnayake, A.R.M.H.A.; Navarathna, S.B. (My University, 2017)
Present dietary scenario necessitates exploring the possibility of incorporating novel ingredients that can improve quality in commonly consumed foods.Moringa olifera is abundant in subtropical regions that is an excellent source of beta carotene and other vitamins, minerals and amino acids.This study was conducted to determine effect of cutting and steam blanching before dehydration on organoleptic properties and dehydration pattern of Moringa olifera leaves. Fresh leaves were harvested from same location and dehydrated under four conditions according totwo factor factorial design. Organoleptic properties of dehydrated leaveswere compared forfour sensory attributes ascolour, aroma, taste and overall acceptability using five point hedonic scale. L*a*b* values were determined and drying curves were plotted for each treatment combination. Results revealed that, blanching and cutting can darker the colour and alter the flavour of dehydrated products.Further the surface area of the leaves have a significant effect in dehydrating time while blanching can accelerate the rate of moisture removal.
Keywords: Blanching, Cutting, Dehydration, Moringa, Sensory properties.